A Prospective Cohort Study on Factors of Mortality Due to Acute Organophosphate Poisoning - Muhammad, Shaib; Almani, Khalida Faryal; Ubed-ur-Rehman Mughal; Muhammad Saleh Khaskheli; Rafia Tabassum; Rabbiya Ahmad; Narendar Kumar (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: This study assessed the association of demographic characteristics, causes of poisoning, pre-hospital care, clinical manifestations, and treatment with outcomes of organophosphate poisoning. METHODOLOGY: This prospective cohort study was conducted in the emergency department, medicine wards, and intensive care units of a tertiary care hospital in Sindh, Pakistan, from July 2023 to June 2024. The data were collected using a non-probability purposive sampling technique, as outlined in a questionnaire designed after reviewing the literature. IBM SPSS version 29 was used for analysis using various statistical tools. The categorical variables were presented as frequencies and percentages. A Chi-squared test (Fisher’s exact test where required) was used to determine the association between variables. RESULT: During the study period, 605 patients were enrolled. Organophosphate poisoning (OPP) was prevalent in males (57.2%). Majority of patients were uneducated (70.9%), belonged to rural areas (96.4%), and were aged ?30 years (82%). Poisoning was mainly intentional (92.2%), through oral route (96.9%). Most common clinical manifestation was emesis (55.9%), and circulatory support was provided to 99.3% of patients as a therapeutic intervention. The majority of patients were mildly affected (84.0%) due to OPP, and the death rate was 5.5%. The vital signs, clinical manifestations, interventions, and hospital management had a significant impact on mortality, with p < 0.05. CONCLUSION: This study’s findings emphasize the necessity for healthcare providers to prioritize the rapid assessment and intervention of baseline vitals, typical OPP symptoms, intensive management, duration of hospital stay, and poisoning severity to achieve better outcomes in patients with OPP.